Intrinsic connectivity networks underlying individual differences in control‐averse behavior - Rudorf, Sarah (Hum Brain Mapp, 2018)
When people sense that another person tries to control their decisions, some people will act against the control, whereas others will not. This individual tendency to control‐averse behavior can have far‐reaching consequences, such as engagement in illegal activities or noncompliance with medical treatments. Although individual differences in control‐averse behavior have been well documented in behavioral studies, their neurological basis is less well understood. Here, we use a neural trait approach to examine whether individual differences in control‐averse behavior might be linked to stable brain‐based characteristics. To do so, we analyze the association between intrinsic connectivity networks as measured by resting state functional magnetic resonance imaging and control‐averse behavior in an economic exchange game. In this game, subjects make choices that are either free or controlled by another person, with real consequences to both interaction partners. We find that the individual level of control‐averse behavior can be positively predicted by intrinsic connectivity within the salience network, but not the central executive network or the default mode network. Specifically, subjects with a more prominent connectivity hub in the dorsal anterior cingulate cortex show greater levels of control‐averse behavior. This finding provides the first evidence that the heterogeneity in control‐averse behavior might originate in systematic differences of the stable functional brain organization.